2020
DOI: 10.1007/s13402-019-00486-4
|View full text |Cite
|
Sign up to set email alerts
|

The exosomal integrin α5β1/AEP complex derived from epithelial ovarian cancer cells promotes peritoneal metastasis through regulating mesothelial cell proliferation and migration

Abstract: Purpose Epithelial ovarian cancer (EOC) is one of the most malignant cancers in the gynecologic system. Many patients are diagnosed at an advanced stage with disseminated intra-peritoneal metastases. EOC spreads via both direct extension and transcoelomic spread. However, the interplay between human peritoneal mesothelial cells (HPMCs) and EOC cells is still ambiguous. We hypothesize that integrins (ITG) in HPMCs may play important roles in EOC metastasis. Methods The expression of different integrin subtypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…Although the 5-year survival rate of patients with ovarian cancer has been stable for the past 20 years, it is still at a low level (30%~40%), making it the deadliest tumor in gynecological tumors. 85,[94][95][96] Because its early clinical symptoms are not obvious, nearly 2/3 of the patients are in the late stage at the time of diagnosis. 97 Most (80%) of the patients who died had epithelial ovarian cancer (EOC).…”
Section: Expression Of Dkk1 In Ovarian Cancermentioning
confidence: 99%
“…Although the 5-year survival rate of patients with ovarian cancer has been stable for the past 20 years, it is still at a low level (30%~40%), making it the deadliest tumor in gynecological tumors. 85,[94][95][96] Because its early clinical symptoms are not obvious, nearly 2/3 of the patients are in the late stage at the time of diagnosis. 97 Most (80%) of the patients who died had epithelial ovarian cancer (EOC).…”
Section: Expression Of Dkk1 In Ovarian Cancermentioning
confidence: 99%
“…A member of the integrin family, ITGA5 often combines with ITGB1 to form integrin α5β1, which serves as a receptor for cell differentiation, cell development, and migration. 11 Altered expression of ITGA5 has been demonstrated in certain cancers, including colorectal, breast, and oral cancers. [12][13][14] In this study, we confirmed that miR-27b was significantly downregulated while ITGA5 was significantly upregulated in TSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, our group has previously shown that Snail expression is regulated by ERK and an autocrine loop involving transforming growth factor beta (TGFβ)/Src/focal adhesion kinase (FAK) complex in thyroid cancer cells [ 28 ]. Similarly, other authors have demonstrated that FAK activation induces Snail expression and enhances mesothelial cell migration, promoting peritoneal metastasis from ovarian cancer [ 54 ]. Moreover, the JNK pathway activates migration by inducing the phosphorylation of paxillin, which is an adaptor protein related to FAK activation in different cancer cells [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 80%